Analysis of the Impact of Transportation Infrastructure Development on Traffic Performance in NTB Province - Efendhi Prih Raharjo; Annisa Mahadita Candrarahayu; I Kadek Surya Putra Adidana (Jurnal Teknologi Transportasi dan Logistik, 2022)
Transportation development is carried out with the construction of various infrastructures. In order to support the realization of safe and peaceful conditions, it is necessary to provide transportation infrastructure and facilities to support the acceleration of regional development, including underdeveloped areas and border areas. then the role of transportation is needed to bridge the gap and encourage the distribution of development results. Development of transportation infrastructure is also being carried out in West Nusa Tenggara Province, which is experiencing transportation development. It was noted that from 2016 to 2020 there were 49 infrastructure developments and developments in both the traffic and road transport sector as well as the ASDP sector. The purpose of this study was to evaluate and determine the impact of existing transportation infrastructure development in West Nusa Tenggara Province in the period 2016 to 2020 through aspects of benefits and traffic performance. The method used is quantitative by obtaining data which is then analyzed by gap analysis. The results of the study show that in the administrative aspect, the usability aspect, and the road performance aspect, it has a good impact on the community, even though in the road performance aspect there are several national roads that do not meet the network speed target.